arctan ( x 1 ) − arctan ( x + 1 1 ) = arctan ( 2 ( x + 1 ) 1 )
Determine the value of x that satisfies the equation above.
If you believe that there are multiple values of x that work, input the sum of all possible solutions as your answer.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
arctan x 1 − arctan x + 1 1 tan ( arctan x 1 − arctan x + 1 1 ) 1 + x ( x + 1 ) 1 x 1 − x + 1 1 x 2 + x + 1 1 ⟹ x 2 + x + 1 x 2 − x − 1 ⟹ x = arctan 2 ( x + 1 ) 1 = tan ( arctan 2 ( x + 1 ) 1 ) = 2 ( x + 1 ) 1 = 2 x + 2 1 = 2 x + 2 = 0 = 2 1 ± 5
{ x = 2 1 + 5 x = 2 1 − 5 L H S = arctan 1 + 5 2 − arctan 3 + 5 2 > 0 L H S = arctan 1 − 5 2 − arctan 3 − 5 2 < 0 R H S = arctan 3 + 5 1 > 0 R H S = arctan 3 − 5 1 > 0 Accepted Rejected
Therefore, the answer x = 2 1 + 5 ≈ 1 . 6 1 8 .
Problem Loading...
Note Loading...
Set Loading...
By the following identity arctan ( a 1 ) − arctan ( b 1 ) = arctan ( a b + 1 b − a ) if a = x and b = x + 1 , we have arctan ( x 2 + x + 1 1 ) = arctan ( 2 ( x + 1 ) 1 ) where equality holds if x 2 + x + 1 = 2 ( x + 1 ) Simplifying, we see that x 2 − x − 1 = 0 , the polynomial that is famous for having the golden ratio 2 1 + 5 and 2 1 − 5 as the solutions. However, since 2 1 − 5 doesn't satisfy the given equation, the golden ratio is the only solution that works.
Remark : Another way to show that 2 1 − 5 does not satisfy the equation is to consider the following diagram:
Here,
∣
A
B
∣
=
1
,
∣
B
C
∣
=
x
,
∣
B
D
∣
=
x
+
1
and
∣
B
E
∣
=
2
(
x
+
1
)
Because
Δ
A
B
C
,
Δ
A
B
D
and
Δ
A
B
E
all share common side
A
B
with length
1
, then
∠
A
C
B
,
∠
A
D
B
and
∠
A
E
B
are all less than
9
0
∘
. In this case,
x
,
x
+
1
,
2
(
x
+
1
)
>
0
. Otherwise, if
m
∠
A
C
B
≥
9
0
∘
, the given equation doesn't hold.